Determination and health risk assessment of trace elements in the tap water of two Sub-Cities of Addis Ababa, Ethiopia. Issue 5 (May 2021) - Dessie, Bitew K.; Gari, Sirak Robele; Mihret, Adane; Desta, Adey F.; Mehari, Bewketu
Abstract: Water is an essential component of all living things on earth and the contamination of water by heavy metals can cause detrimental health effects. This study aimed to determine the health risk posed by trace elements (Fe, Zn, Cu, Mn, Ni, Cr, Cd, Co, Pb, and As) present in the drinking water supplies of Gullele and Akaki-Kality Sub-Cities, upstream and downstream parts of Addis Ababa, respectively. The concentrations of the potentially toxic trace elements in the water samples were determined using inductively coupled plasma optical emission spectroscopy (ICP-OES). The highest concentration of the heavy metals was observed for Iron. Cadmium and cobalt were not detected in any of the tap water samples. Samples from Gullele contained higher levels of Fe and Mn, 220.3 ± 0.17 and 19.78 ± 0.08 μg/L, respectively compared to Akaki-Kality, 38.87 ± 0.14 and 2.08 ± 0.01 μg/L, respectively. Conversely, tap water from Akaki-Kality contained significantly higher levels of As than that from Gullele. Additionally, Cr and Ni were detected only in samples from Akaki-Kality, which might be due to the various industries in the area. The highest incremental lifetime cancer risk was found for arsenic, with values for children and adults in Akaki-Kality 2.50 × 10 −4 and 4.50 × 10 −4, respectively. Likewise, in Gullele Sub-City, it was 5.00 × 10 −5 and 1.00 × 10 −4 for adults and children, respectively. The results indicate that carcinogenic risk occurrence is probable from As in both studied areas. Abstract : Water quality; Trace elements; Chronic daily intake; Hazard quotient; Incremental lifetime cancer risk; Addis Ababa, Ethiopia